Respons Metabolik terhadap Pembatasan Asupan Pakan pada Kambing Peranakan Ettawa (METABOLIC RESPONSES TO FOOD RESTRICTION IN ETTAWA CROSSBRED GOATS) - Widiyono, Irkham; ., Sarmin; Suwignyo, Bambang (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
The study aim of this  was to evaluate the effects of food restriction on metabolic aspects (bloodchemistry parameters) in Ettawa crossbred goats. Four adult male and clinically healthy Ettawa crossbredgoats were used in this study. The animals were kept in individual cage for 12 weeks. Animal feed consistedof aerial part of peanut plant and concentrate at a ratio of 60:40. The experiment was devided into 2phases of feeding periods, fullfeeding (ad libitum  feeding and restricted feeding. After the adaptationperiod for 4 weeks (week 1-4), the animals were fed ad libitum for 4 weeks (week 5-8), and then continuedwith 50% of the ad libitum feed intake during the following 4 weeks restricted feeding period (week 9-12).During the experiment, drinking water was supplied ad libitum. Body weight were examined and bloodsamples were collected at the end of the fullfeeding and restricted feeding periods for blood chemistryanalyses. Statistical differences were determined by paired t-Test at probability level of 0.05. This studyshowed that feed restriction up to about 50% of ad libitum (80% of maintenance) feed intake resulted inchanges of blood chemistry parameters. At the end of restricted feeding period, the elevated concentrationof serum inorganic phosphate, creatinine, blood urea nitrogen, and cholesterine were observed and reducedconcentration of glucose, calcium, and triglyceride were observed. However no change was observed on  levelof arterial blood pH and the concentration of serum natrium, potassium, chloride, and protein. In conclusion,nutritional status has significant effect on blood chemistry parameters of Ettawa crossbred goats. Seruminorganic phosphate, calcium, creatinine, blood urea nitrogen, cholesterine, glucose, and triglycerideconcentration could provide the more reliable information for assessment of the nutritional status ofEttawa crossbred goat.
Keywords: Ettawa crossbred goat, food restriction, blood chemistry